Preliminary study for development electronic student worksheet in biology - Hiola, St Fatmah; Saleh, Andi Rahmat; Rusli, Anisa (JURNAL ATRIUM PENDIDIKAN BIOLOGI, 2023)
This study aims to analyze the needs of the development of electronic student worksheet on kingdom plantae material. The subjects in this study were 3 biology teachers and 29 students of class X SMA Negeri 1 Wonomulyo. This type of research is descriptive. Data collection techniques used are interviews and questionnaires. The results of the study showed that students received material using lecture, question and answer, demonstration methods and were assisted by learning media, there was already a presentation of the student worksheet given but only on certain material. Student worksheet is impressed as a tool for writing and copying, and looks less attractive. In addition, the use of gadgets and laptops during learning is still not optimal. Students experience difficulties in understanding the differences in each division and class in kingdom plantae. Teachers and students are interested in using electronic student worksheet. Therefore, the solution that can be done is to develop an electronic student worksheet on kingdom plantae material.